Adsorption of Crystal Violet Dye from Aqueous Solution Using Ricinus Communis Pericarp Carbon as an Adsorbent - S. Madhavakrishnan; K. Manickavasagam; R. Vasanthakumar; K. Rasappan; R. Mohanraj; S. Pattabhi (E-Journal of Chemistry)
Carbon prepared from Ricinus Communis Pericarp (RCP) was used to remove a crystal violet dye from aqueous solution by an adsorption technique under varying conditions of agitation time, dye concentration, adsorbent dose and pH. Adsorption is influenced by pH, dye concentration, carbon concentration and contact time. Equilibrium was attained with in 60 min. Adsorption followed both Langmuir and Freundlich isotherm models. The adsorption capacity was found to be 48.0 mg/g at an initial pH of 6.8±0.2 for the particle size of 125–250 μm.